Analysis of Decision Support System in Determining the Nutritional Status of Toddlers Using Simple Additive Weighting - Ofan Sofian; Joseph Joseph; Fauziyah Fauziyah (Bina Nusantara University, 2020)
The problem that currently happens in the decision process of the nutritional status for toddlers is often based on manual calculation. However, the manual calculation is prone to data duplication, insufficient data, and a lack of availability of the data itself, which can hinder the monitoring status and the report. Therefore, to ease the determination and calculation process of the nutritional status of toddlers, the researchers conduct a study using the Simple Additive Weighting (SAW) method. The SAW method is selected because it defines the best alternative and some other alternatives based on specified or preferred criteria. This research is conducted by finding the weight value of each attribute and rating the data to determine the nutritional status of toddlers. For the result, the researchers find there are no toddlers with malnutrition in Pemberdayaan Kesejahteraan Keluarga, Program Kerja Kelompok Kerja IV (PKK POKJA IV) of Depok.